2020
DOI: 10.4012/dmj.2020-016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects on <i>Streptococcus mutans</i> of antibacterial agents mixed with experimental fluoride varnish

Abstract: We investigated the inhibitory effect of antibacterial agents mixed with experimental fluoride varnish (EFV) on Streptococcus mutans. The antibacterial agents used were (1 and 10) mM of xanthorrhizol, bakuchiol, bavachalcone, isobavachromene, and bavachromene. Agar diffusion tests were performed on S. mutans (1.1×10 10 CFU/mL), using antibacterial agents without and with EFV. Bavachalcone showed the highest inhibition zone without and with EFV at both (1 and 10) mM (p<0.05). All EFV with antibacterial agents s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…With regard to the sustainability of antibacterial activity, CA showed a higher antibacterial effect when mixed with the experimental FV than when the FV was applied alone. FV is clinically very effective in preventing dental caries and has a slight antibacterial effect 18,[25][26][27][28] . The experimental FV was used as a vehicle or carrier for CA in the study, and we confirmed that the antibacterial effect was sustained for up to 3 days when CA was combined with the FV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the sustainability of antibacterial activity, CA showed a higher antibacterial effect when mixed with the experimental FV than when the FV was applied alone. FV is clinically very effective in preventing dental caries and has a slight antibacterial effect 18,[25][26][27][28] . The experimental FV was used as a vehicle or carrier for CA in the study, and we confirmed that the antibacterial effect was sustained for up to 3 days when CA was combined with the FV.…”
Section: Discussionmentioning
confidence: 99%
“…To serve as a vehicle for CA in the antibacterial activity sustainability test, a FV was prepared as follows: 45 wt% rosin (KR-610, Arakawa Chemical Industries, Osaka, Japan), 50 wt% solvent (ethanol, absolute ≥99.7% purity, Merck, NJ, USA), and 5 wt% sodium fluoride were mixed using an overhead stirrer (RW20DZM.n, IKA Korea, Seoul, Korea) at 240 rpm for 30 min in a double boiler at 80-100ºC on a hot plate (RCH-3, Tokyo Rikakikai, Tokyo, Japan) 18) .…”
Section: Preparation Of the Experimental Fluoride Varnish (Fv)mentioning
confidence: 99%
“…When the efflux pump components (AcrAB, TolC) were absent or in the presence of efflux pump inhibitors, the antibacterial activity of IBC was significantly increased (Kuete et al, 2010). IBC can bind well to the surface protein SrtA of S. mutans, thus showing an inhibitory effect on S. mutans (Salmanli, Tatar Yilmaz, & Tuzuner, 2021; Son, Kim, Oh, & Bae, 2020). IBC also has certain antibacterial activity against Mycobacterium tuberculosis (Chiang et al, 2010; Pollo et al, 2020).…”
Section: Pharmacological Effects Of Ibcmentioning
confidence: 99%
“…However, pathogenic bacteria can acquire antibiotic resistance and facilitate the dysbiosis of microbial flora in the human body 11) . Therefore, phytochemicals have received increasing attention as potential antibacterial agents owing to the fewer side effects than antibiotics [12][13][14][15] . Periodontal disease can be managed via a local drug delivery system, in which medication is injected directly into the periodontal pocket to maintain an effective concentration [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%